2019
DOI: 10.1002/app.47536
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane‐based poly (ionic liquid)s for CO2 removal from natural gas

Abstract: Carbon dioxide separation from CH 4 is important to the environment and natural gas processing. Poly (ionic liquid)s (PILs) based on polyurethane structures are considered as potential materials for CO 2 capture. Thus, a series of anionic PILs based on polyurethane were synthesized. The effects of polyol chemical structure and counter-cations (imidazolium, phosphonium, ammonium, and pyridinium) in CO 2 sorption capacity and CO 2 /CH 4 separation performance were evaluated. The synthesized PILs were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…For SIL and SIL-Cl samples an increase in temperature resulted in a decrease on CO 2 sorption capacity, indicating typical behavior of a physical sorbent. Similar behavior was described in litertura (Bernard et al., 2019; Ye et al., 2012). For SIL-OAc the temperature increase improves the interaction between [OAc] - and CO 2 molecules increasing CO 2 sorption capacity.…”
Section: Resultssupporting
confidence: 81%
“…For SIL and SIL-Cl samples an increase in temperature resulted in a decrease on CO 2 sorption capacity, indicating typical behavior of a physical sorbent. Similar behavior was described in litertura (Bernard et al., 2019; Ye et al., 2012). For SIL-OAc the temperature increase improves the interaction between [OAc] - and CO 2 molecules increasing CO 2 sorption capacity.…”
Section: Resultssupporting
confidence: 81%
“…The incorporation of sulphate and sulphonate anions produces highly resilient PILs through the presence of irreversibly cross-linked ion pairs [ 211 , 212 , 213 , 214 ]. Similar stability can be achieved by the incorporation of hydroxide, carbonate, phosphate, and phosphonate anions [ 121 , 179 ]. These anions provide thin films that exhibit not only reversible CO 2 solubility, but also that resist the hydrolysis of anionic groups.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 96%
“…A broad variety of PU-based PILs has been prepared to investigate the influence of different ionic diols as cations and counterions on the CO 2 selectivity [ 178 , 179 ]. Further research on their application in CO 2 /CH 4 separation demonstrated the possibility of PU-based PILs to overcome the CO 2 sorption capacity in comparison to linear PILs [ 121 ]. Furthermore, several hybrid urethane-imide PILs showed enhanced CO 2 sorption capacity in the CO 2 physisorption experiments [ 180 ].…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
“…Results provide evidence that the addition of CPIL-TBP can increase the selectivity of PU for CO 2 over CH 4 . PU/CPIL-TBP 20% composite presented higher CO 2 /CH 4 selectivity as compared with polyurethane-based poly(ionic liquid) s (PILPC-TBP: CO 2 /CH 4 selectivity of ∼2.22 at 303.15 K and 2 MPa) 49 and PU foam/ILs composite (PUF BF4 40: CO 2 /CH 4 selectivity of 1.42 at 3 MPa) 29 .…”
Section: Tensile Properties and Young Moduli Are Presented Inmentioning
confidence: 96%